EFFECTIVENESS OF ONLINE SALES TECHNIQUES VIA LIVE SHOWS: BASED ON ONLINE SHOPPING EXPERIENCE, PRODUCT SUITABILITY AND PURCHASING POWER IN FOLLOWING ONLINE SHOPPING TRENDS - David Hamonangan Simamora; Hendra Jonathan Sibarani; Andreas Alvin Liadi; Sari Mariahma Nova Sipayung (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Online shop is an alternative form that can be used by business people to offer products or services to consumers as the number of internet users continues to grow. Sales through live shows are not only available in the Tiktok application, but also in e-commerce and social media such as Shopee, Tokopedia, Facebook, Instagram, Lazada and many others. The purpose of this study is to test and analyse the online shopping experience, product suitability and purchasing power with the effectiveness of online sales techniques via live shows. The research method is quantitative research with data analysis techniques using Partial Least Square (PLS) analysis including outer model analysis, inner model and partial and simultaneous hypothesis testing. The population and sample in this study were residents of sub-districts in Medan Petisah who had characteristics as respondents who used live shows in sales techniques and product offerings as many as 100 respondents. The results of the study obtained online shopping experience with a t-statistic value of 1.987 > 1.66 and p-values 0.048, product suitability with a t-statistic value of 3.951 > 1.66 and p-values 0.000, while in purchasing power has a t-statistic value of 2.276 > 1.66 and p-values 0.023, which means that the variables of online shopping experience, product suitability and purchasing power have a positive and significant effect on the effectiveness of online sales via live shows.